Synthetic essentiality of chromatin remodeling factor CHD1 in PTEN deficient cancer - Zhao, Di (Nature, 2017)
Synthetic and collateral lethality have provided conceptual frameworks to identify cancer-specific vulnerabilities(1–3). Here, we explored an approach to identify potential synthetic lethal interactions through screening mutually exclusive deletion patterns in cancer genomes. We sought to identify ‘synthetic essential’ genes, which might be occasionally deleted in some cancers but almost always retained in the context of a specific tumor suppressor deficiency, and posited that such synthetic essential genes would be therapeutic targets in cancers harboring specific tumor suppressor deficiencies. In addition to known synthetic lethal interactions, this approach uncovered the chromatin helicase DNA-binding factor CHD1 as a putative synthetic essential gene in PTEN-deleted cancers. In PTEN-deleted prostate and breast cancers, functional analysis showed that CHD1 depletion profoundly and specifically suppressed cell proliferation, survival and tumorigenic potential. Mechanistically, functional PTEN stimulates GSK3β-mediated phosphorylation of CHD1 degron domains, which promotes CHD1 degradation via β-TrCP-mediated ubiquitination-proteasome pathway. Conversely, PTEN deficiency results in CHD1 protein stabilization, which in turn engages the H3K4me3 mark to activate transcription of the pro-tumorigenic TNFα/NF-κB gene network. Together, this study identifies a novel PTEN pathway in cancer and provides a framework for the discovery of trackable targets in cancers harboring specific tumor suppressor deficiencies.